Women’s Subversive Strategies Against Patriarchy in The Modern Thrillers Story Where the Crawdads Sing by Owen and Gone Girl by Flynn - Aida Hanissa; Rahayu Puji Haryanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This article discusses women's subversive strategies against patriarchy in two modern thriller novels, Where the Crawdads Sing by Delia Owens and Gone Girl by Gillian Flynn, using feminist theory with The Madwoman in the Attic as the basis of analysis. This article focuses on how the patriarchal conditions in the two novels give rise to subversive strategies of the female characters in the two novels that represent women and how they impact on the two novels. Based on the text analysis, Amy Dunne uses narrative manipulation and idealized female imagery to assert language as a tool of liberation and reverse power, while Kya Clark uses self-reliance and connection to nature to resist patriarchy and construct an identity beyond social norms. These strategies create complex tensions and conflicts that challenge stereotypes of passive women and present women as creative, empowered and active agents. In summary, these two novels demonstrate that women's resistance to patriarchy can be realized in unique and extreme ways, changing the meaning of women in contemporary literature and enhancing gender dynamics in the thriller genre.